Torch Bearer, Weary Juggler, and Heckler: Representations of Teacher Leadership - Stout, Rosana; Cumming-Potvin, Wendy; Wildy, Helen (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2017)
This paper is drawn from a mixed methods study, which examined the leadership practices of teachers in the Level Three Classroom Teachers program in Western Australia. Three archetypal characters, the Torch Bearer, Weary Juggler, and Heckler, are used to represent the diverse leadership experiences of these “expert” teachers and the extent to which they embraced or resisted policy constructions of teacher leadership. Narrative analysis and the construction of these representations provided the means of inserting teachers’ voices and problematizing dominant discourses on teacher leadership in a way that invites policymakers to reconsider the larger narrative of teacher leadership, along with the personal dimension of leadership work.